Serum albumin and blood urea as independent predictors of in-hospital mortality in hospitalized COVID-19 patients: A retrospective cohort study - Nuha Al-Aghbari (PLoS ONE, 2026)
Background While systemic inflammation is a hallmark of severe COVID-19, the prognostic value of metabolic and organ-functional markers remains under-explored. This study examined the prognostic value of serum albumin and blood urea at hospital admission in predicting in-hospital mortality among patients with COVID-19. Methods We performed a retrospective cohort study of 1,074 adult patients with laboratory-confirmed COVID-19 who were hospitalized in a tertiary care center. Patients’ demographic, clinical and laboratory data on admission were collected from electronic medical records. We conducted multivariable logistic regression analyses to determine independent predictors of in-hospital death after adjusting for possible confounders including age, sex, comorbidities and known inflammatory/coagulation markers. Missing laboratory variables were imputed by multiple imputation by chained equations. Area under the receiver Operating characteristics curve (AUC) was evaluated for model discrimination. Results In-hospital mortality occurred in (24.5%). Non-survivors had significantly lower serum albumin and higher blood urea levels at admission. After full adjustment, hypoalbuminemia remained independently associated with increased mortality risk. Each 10 mg/dL increase in urea was associated with a 14% increase in the odds of death (AOR = 1.14, 95% CI 1.08–1.20), whereas albumin demonstrated an independent protective association with mortality (AOR = 0.52, 95% CI 0.37–0.74). The final multivariable model demonstrated good discrimination (AUC = 0.86), indicating strong predictive ability. Conclusions Serum albumin and blood urea at hospital admission independently predict mortality in patients with COVID-19, even after accounting for inflammatory and coagulation markers. These findings suggest that markers of organ-functional reserve may provide prognostic information beyond traditional inflammatory markers in hospitalized patients with COVID-19.